Thinktastic Blend: Strategi Mindfullness Mengembangkan Keterampilan Berpikir Kritis, Kreativitas dan Tanggung Jawab - Maysarah, Lia; Agusta, Akhmad Riandy (Raja Zulkarnain Education Foundation, 2025)
The background of this study is the low level of student engagement and the lack of creativity, critical thinking skills, and sense of responsibility among students. The use of the Thinktastic Blend model, which combines SQ3R, project-based learning, and Literacy-Based Instruction methodology, is estimated to be effective in improving creativity, critical thinking skills, and sense of responsibility in Indonesian language learning. This study aims to improve critical thinking skills, creativity, responsibility, activeness, and student learning outcomes in Indonesian language subjects. This study took place in the even semester of the 2024/2025 academic year in class V-A SDN-SN Pasar Lama 3. In this study, 20 students participated in four learning meetings using a classroom action approach. Test instruments were used to collect data on creativity, critical thinking skills, and sense of responsibility, which were compiled based on test specifications to meet the requirements for a valid test. Another instrument in this study was an observation guide to obtain data on student activities in learning using the Thinktastic Blend model. Documentation techniques were also used in this study. The findings of this study indicate improved learning outcomes in Indonesian language subjects through increased creativity, critical thinking skills, a sense of responsibility, and teacher and student engagement. In other words, the use of the Thinktastic Blend model has proven successful in improving learning outcomes and the Indonesian language learning experience.